Kinerja Dinas Pariwisata Dalam Meningkatkan Pariwisata Di Kota Padang Pasca Covid-19 - Putra, Muhammad Furqan Oktowita; Adnan, M. Fachri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This research found several problems, namely the Tourism Sector in the City of Padang almost collapsed due to the Covid 19 Pandemic, losses due to the Covid 19 pandemic not only had an impact on the implementation of tourism directly, but also on the tourism supporting industrial sector such as transportation/travel services, hotels, and tourism. so on. The absence of tourist visits, both domestic and foreign, has caused many tours to be closed, the majority of the hotels have also experienced a decline and this means that there is no income for people who work in the tourism sector and budget revenues for the provincial government of West Sumatra. This research was conducted with a descriptive approach, qualitative data survey method, the selection of informants was carried out using a purposive sampling technique, and the validity of the data was tested using a triagulation technique. Data was collected by interview, study documentation and observation. The researcher uses the theory from Mustopadjadja (2003) there are five indicators, namely Input, Process, Output, Benefits, Impact. The results show that in the Performance of the Tourism Office in Improving Tourism in the City of Padang Post Covid 19, the policies issued are still weak tourist visits. to tourist attractions, various efforts made by the Tourism Office such as collaborating with other agencies in providing guidance/socialization to tourism and industry actors with assistance to hotels and restaurants affected by the pandemic. However, it is still not enough to help restore the economy of the affected communities.